EXPLAINING THE ROLE OF THE MEDIA IN REDUCING AND CONTROLLING ECONOMIC CORRUPTION (AN ANALYSIS ON THE BASIS OF GROUNDED THEORY APPROACH) - Aboutrab Talebi, Farshad Momeni, Esmaeil Shojaei (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this research is to investigate how the media influence the reduction and control of economic corruption. In terms of data, our research is qualitative exploratory and is cross-sectional in terms of data collection time and a survey in terms of data collection method. The statistical population of the research includes economists, sociologists, communication and media experts, Political Science Specialists; Senior economic managers such as economic deputies of ministries; Senior private sector executives from the Chamber of Commerce and the editors of economic newspapers and magazines. Purposeful non-random sampling method was used to determine the samples of this research. To ensure the validity of the tool in the qualitative part of the research, we benefited from the valuable opinions of professors familiar with this field and university experts who were experts in this field. The method of data analysis in the qualitative part was theoretical coding. The results showed that among the 405 indicators extracted from interviews with experts, 21 main components can be extracted that can be categorized in the form of main phenomena, causal conditions, and consequences.